PENGARUH PENKES TERHADAP KECEMASAN IBU PADA BALITA YANG DILAKUKAN PEMASANGAN INFUS DI RS SILOAM SRIWIJAYA PALEMBANG - Sri Hartati; Shinta Maharani; Pebrin Gultom; Lela Aini (Institut Kesehatan dan Teknologi Al Insyirah, 2021)
ABSTRACT One of the invasive procedures performed on children is therapy via intravenous (intravenous infusion). Anxiety experienced by parents can immediately be seen from changes in their behavior disorders. In this situation, the nurse's role as a source of information and support for the family. Information from medical personnel is needed for parents to monitor their child's condition time after time. Support for mothers as parents of children admitted to hospitals explains that parents feel calmer when the nursing team is able to provide support so that they are able to form positive coping. This type of research is quantitative with pre-experimental research design using one group pretest posttest approach. The population in this study were all mothers who have children under five years old at Siloam Sriwijaya Hospital Palembang in 2019, while the number of samples taken in this study were 20 respondents. The results of the analysis showed that the average score of maternal anxiety in infants who had infused infants before being given health education was 59.00 and a standard deviation of 3.00. The maternal anxiety score for toddlers who underwent infusion before being given the lowest health education was 55 and the highest score was 65. The average anxiety score of mothers in toddlers who underwent infusion after being given health education was 52.90 and the standard deviation was 4.45. The maternal anxiety score for toddlers who performed infusion of toddlers after being given the lowest health education was 45 and the highest score was 61. There was an influence of health education on maternal anxiety for toddlers who performed infusion of toddlers at Siloam Sriwijaya Hospital Palembang in 2019 (ρ = 0,000) , with a difference in average score of 6.1 .. As for the advice given to the Officer not only focuses on physical assessment but also assesses the psychological parent of the child so that mothers who have abnormal anxiety get the right treatment. Key Words : Health Education, Anxiety, Toddler Infusion Installation